3D Finite Element Modeling of Single Bolt Connections under Static and Dynamic Tension Loading - Emily Guzas; Kevin Behan; John Davis (Shock and Vibration)
The Naval Undersea Warfare Center has funded research to examine a range of finite element approaches used for modeling bolted connections subjected to various loading conditions. Research focused on developing finite element bolt representations that were accurate and computationally efficient. A variety of finite element modeling approaches, from detailed models to simplified ones, were used to represent the behavior of single solid bolts under static and dynamic tension loading. Test cases utilized models of bolted connection test arrangements (static tension and dynamic tension) developed for previous research and validated against test data for hollow bore bolts (Behan et al., 2013). Simulation results for solid bolts are validated against experimental data from physical testing of bolts in these load configurations.